2005
DOI: 10.1108/00012530510612059
|View full text |Cite
|
Sign up to set email alerts
|

Accountability and accessibility: ensuring the evidence of e‐governance in Australia

Abstract: Purpose -To review the challenges associated with ensuring the capture and preservation of and long-term access to government records and publications in the digital age and to describe how libraries and archives in Australia are responding to the challenge. Design/methodology/approach -Literature-and case-study-based conceptual analysis of what makes government online information so vulnerable and initiatives at the National Library of Australia and the National Archives of Australia. Findings -Democracy, gov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
10
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 4 publications
1
10
0
Order By: Relevance
“…Departmental libraries have a role in providing public access by collecting and organising internal publications and possibly have a role in carrying out the legal deposit requirements of section 210 of the Copyright Act, 1968 (Cunningham & Phillips, 2005;Lin & Eschenfelder, 2010). A search in the catalogue of the National library shows that a print copy of the final report of the Independent Media Inquiry is available but not the submissions.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Departmental libraries have a role in providing public access by collecting and organising internal publications and possibly have a role in carrying out the legal deposit requirements of section 210 of the Copyright Act, 1968 (Cunningham & Phillips, 2005;Lin & Eschenfelder, 2010). A search in the catalogue of the National library shows that a print copy of the final report of the Independent Media Inquiry is available but not the submissions.…”
Section: Discussionmentioning
confidence: 99%
“…While there is much other textual content written specifically for websites, consideration of this material is not included in this research paper. A decade ago Cunningham and Phillips (2005) outlined the challenges to the securing of access to government information, specifically grey literature, and since then a 2009 study on e-government reported 32 per cent of the Australians surveyed had used the Internet to search for 'parliament/government information' (Gauld, Goldfinch, & Horsburgh, 2010, p. 180). The questions therefore must be asked, are government documents easily and permanently accessible to the public, and what policies, responsibilities, decisions and institutional mechanisms are in place to achieve this default position of open government.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Records and recordkeeping are crucial for good governance by enabling transparency, accountability, efficiency, predictability and protection of human rights (Dikopoulou and Mihiotis, 2012;Cunningham and Philips, 2005;Lemieux, 2001). The purpose of accountability is to ensure "honest, responsible, upright and transparent conduct of human affairs" (Hurley, 2005, p. 226).…”
Section: Accountability and Trustmentioning
confidence: 99%
“…In cases of corruption or failure of accountability, part of the reason is mostly also a failure of recordkeeping practices (Hurley, 2005). Long-term preservation of records enables accountability over both distance and time (Cunningham and Philips, 2005). Keeping records is not enough though; it has to be connected to rules and mandates to carry out accountability processes.…”
Section: Accountability and Trustmentioning
confidence: 99%